Strategy for Recovery from Indonesian Financially Distressed Companies in Crisis - Wijantini (International Research Journal of Business Studies, 2020)
At the time of writing, the International Monetary Fund (IMF) declared a global economy recession due to pandemic crisis. The spread of coronavirus shut down many companies and put them in financial distress. Many previous studies investigate the strategy for firms’ recovery in normal economic condition. However, firms may adopt different strategies during crises. The Asian crisis is a well-known example of a temporary, but stiff contraction across industries. In this case, troubled firms demand certain corporate strategies to recover from the crisis. The main purpose of this study is to undertake an empirical examination of Indonesian financially distressed firms as they strive to recover during the severe crisis. It compares the strategy between recovered and non-recovered firms. Successful strategies for recovery are identified through Altman’s Emerging Market Score. The strategies involve four types of restructuring such as operational, financial, asset, and management restructuring. This study uses the number of employees decreased, debt restructuring, disposal of assets, and change of the CEO as the proxy of the respective types of restructuring. The success of debt restructuring appears to be the most important differentiator of recovery.